Determinants of Incident Risk of Acute Respiratory Infection in Infants in Populated City - Fitriana Kurniasari Solikhah (Journal of Global Pharma Technology, 2020)
Introduction: Acute Respiratory Infection (ARI) was a major cause of morbidity and mortality in infants. ARI was always ranked first of the 10 most diseases in Indonesia. To be able to overcome the spread of ARI, it was necessary to know the risk factors for ARI. The purpose of this study was to analyze the relationship of predisposing factors (education, family income, knowledge, and attitudes), supporting factors (use of health care facilities, ventilation, presence of smokers in the house), driving factors (the role of health workers) with the risk of ARI events recurrent pneumonia in infants. Methods: This type of research was descriptive analysis with a cross-sectional approach. Data collection was done by questionnaire. The population was parents of children under five in the working area. This study used purposive sampling, with a sample of 100 respondents. Data analysis was done by univariate, bivariate with chi-square test and odds ratio. Results: The results showed that the incidence of recurrent Non Pneumonia ARI in toddlers had a significant relationship with knowledge (p-value = 0.017; OR = 0.27, attitude (p-value = 0.003; OR = 0.27), use of health care facilities ( p-value = 0.371; OR = 0.58), ventilation (p-value = 0.028; OR = 0.29), smokers in the house (p-value = 0,000; OR = 7.56), the role of health workers (p-value = 0,000; OR = 0.17). Conclusion: Recommendations need further research to develop a model of prevention of recurrent Non-Pneumonia ARI in infants according to the risk factors of the incident found so that it can.Keywords: Acute Respiratory Infection, Infants, Risk factor.